Analisis Literatur : Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover - Putra, Ridho Maha; Perkasa, Didin Hikmah; Saluy, Ahmad Badawi (Economic Reviews Journal, 2025)
The costs associated with hiring, training, and losing important organizational expertise make high employee turnover rates a major issue for businesses. This study examines the interplay between employees' intentions to depart and organizational commitment and job satisfaction. Using a qualitative methodology Including a survey of prior studies, the research summarizes results from a number of indexed journals that were published between 2020 and 2025. According to the investigation, organizational commitment and work satisfaction both have a large and negative impact on the intention to leave. Job satisfaction is essential for employee retention and is determined by factors like pay, working conditions, opportunities for advancement, and supervisor support. Similarly, reducing the probability of turnover requires organizational commitment, particularly its affective and continuation components. In order to effectively retain qualified staff and reduce organizational losses, the study emphasizes the necessity for firms to improve HR policies targeted at increasing employee engagement and happiness. Keywords: Job satisfaction, Organizational commitment, Turnover intention, Employee retention, Human resource strategy